The positive impact of silicon on the yield and quality of tobacco - He, Mengjie; Li, Qiang; Ma, Ya; Zhou, Pengtao; Kang, Kang; Wu, Boran (Frontiers in Plant Science, 2025)
Silicon (Si) is widely used in agricultural crop practices. However, the effects of varying Si application rates on tobacco growth and quality remain unclear. Therefore, this study applied four different Si concentrations, i.e., 0, 750, 1500 and 3000 kg/ha of Si (S0, S50, S100 and S200), examined the impact of different Si concentrations on tobacco (Nicotiana tabacum L. ‘Yunyan 87’) growth, nutrient utilization, and economic quality under field conditions. The results demonstrated that Si application significantly improved tobacco growth, the biomass significantly increased by 19.5%-26.53%; during button stage, the plant height significantly increased by 15.38%-19%. Si also enhanced nutrient use efficiency, particularly for nitrogen and potassium. The utilization efficiency of N and K fertilizer were significantly increased by 27.42%-43.71% and 40.25% - 44.63%, respectively. Furthermore, Si improved leaf physical properties, enhancing single-leaf weight and leaf area, while reducing leaf density and midrib ratio, optimizing leaf quality by improving the sugar-alkali ratio and potassium-chloride balance. Notably, the reducing sugar content in upper leaves increased by 15.21% with S50 treatment, while the chlorine content in middle leaves was decreased by 11.11% with S100. Additionally, among all treatments, S50 achieved the highest proportion (94.75%) of medium and high-quality tobacco leaves, along with a 15.70% increase in yield and a 30.76% boost in output value compared to S0. However, excessive Si application (3000 kg/ha) negatively affected quality, increasing nicotine levels and disrupting the sugar-alkali ratio, which elevate leaf irritancy. In conclusion, moderate Si application (750–1500 kg/ha) is an effective strategy for enhancing tobacco yield and quality, offering a sustainable approach to optimize cultivation practices.